Research on the Integration and Optimization of Fashion Brand Marketing Strategy in the Digital Age - Liu, Jialing (Asia Pacific Economic and Management Review, 2024)
With the advent of the digital age, the way fashion brands market has undergone profound changes. This paper aims to explore the integration and optimization of fashion brand marketing strategies in the digital era, analyze the challenges and opportunities faced by fashion brands in the process of digital transformation through literature review, and put forward corresponding strategy suggestions. It is found that digital marketing has significant advantages in enhancing brand influence, satisfying consumers’ personalized needs, and realizing precision marketing. However, fashion brands still need to overcome technical, managerial, cultural and other obstacles in the process of digital transformation. The strategy framework and concrete measures proposed in this paper provide a useful reference for fashion brands to achieve sustainable development.